CROSS-BORDER COOPERATION, PROTECTED GEOGRAPHIC AREAS AND EXTENSIVE AGRICULTURAL PRODUCTION IN SERBIA - Stojanovic, Zaklina; Manic, Emilija (Economics of Agriculture, 2018)
The concept of Sustainable Agricultural and Rural Development (SARD) is based on resources effective usage that brings strengthen social cohesion of rural regions. Sustainable agro systems take care of natural resources conservation, as well as of economic and social aspects of rural economy. In order to advance complementary activities, agricultural sector has been often seen as the base for local economical diversification of capacities. The connections between agriculture, nature and tourism are especially important. The EU countries insist on this kind of connections which is the integral part of financial support of common funds, while the candidate countries are using the IPA assistance for rural development programs. Program of cross - border cooperation has been placed within this context, too. The article, also, gives several examples of cross-border cooperation project that might include Serbia with some of the neighboring countries in the area of tourism and rural development. The most important elements of cooperation with comments and issues from the authors perspective of view are given in this paper.